Work-Life Balance and Employee Engagement: A Study on Millennial Employees in Startups - Hendarti, Ricca; Tanjung, Febrina Soraya; Siagian, Mei Veronika Sri Endang (SAFE-Network, 2025)
This study aims to investigate the relationship between Work-Life Balance (WLB) and Employee Engagement (EE) among millennial employees working in startups. With the growing prevalence of startups, understanding the factors that influence employee engagement, particularly in the context of work-life balance, is crucial. A total of 135 millennial employees from various startups participated in the survey, which utilized a structured questionnaire based on existing scales for WLB and EE. The results show that there is a significant positive correlation between work-life balance and employee engagement. Employees who perceive better work-life balance tend to report higher levels of engagement in their work. This finding emphasizes the importance of organizational policies that support work-life balance, such as flexible working hours and work-from-home options, in fostering employee engagement. The study also highlights the need for startups to create a supportive work environment to maintain high levels of employee motivation and job satisfaction. Future research could examine additional factors that influence employee engagement, such as leadership styles and career development opportunities, to further enhance organizational outcomes.